A combined computational and functional approach identifies FBLN5 as an amino acid metabolism-related gene and suppressing colorectal cancer progression - Jiezhi Chen; Yang Bai; Shiyi Liu; Changwei Lin (Molecular Genetics and Genomics, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Enhancing the oral processing and swallowing performance of cod soft gels - Xiliang Yu; Yue Wang; Lin Han; Shiyi Liu; Michelle Ji Yeon Yoo; Xiuping Dong (Journal of Food Engineering, 2026)

Inertial-buoyant coupling and bi-directional flow effects on plume deflection in inclined tunnel fires under natural ventilation - Tianhang Zhang; Lei Liu; Ke Wu; Shaorun Lin; Shiyi Wang; Xin Zhang (Tunnelling and Underground Space Technology, 2026)

Photocatalytic hydrogen production: Materials design, system engineering, and data-driven advances - Gengran Zhai; Junchen Liu; Shiyi Lin; Yifan Cheng; Bin Wang; Qingyao Jiang; Hongwei Fu; Hongxin Zhao; Yuan Lu (Chemical Engineering Journal, 2026)

Spurious seasonality in satellite turbidity monitoring driven by K1 tidal aliasing - Shiyi Cao; Qian Yu; Shiyu Zhang; Jie Feng; Yidong Guo; Hangjie Lin; Yunwei Wang (Remote Sensing Applications: Society and Environment, 2026)

Armed covalent organic framework engineered polyamide membranes for highly permeable and selective nanofiltration - Xu Dong; Jiaojiao Cao; Jialei Hou; Hanqi Lin; Chenglin Yang; Zixu Yang; Shiyi Zhu; Runnan Zhang; Hong Wu; Zhongyi Jiang (Desalination, 2026)

Seasonal modulation of the spring-neap response of Yangtze Estuary turbidity maximum: Movement, amplitude, and phase lag via remote sensing - Jie Feng; Qian Yu; Shiyi Cao; Zhiyun Du; Hangjie Lin; Ya Ping Wang; Yunwei Wang (Estuarine, Coastal and Shelf Science, 2026)

Flux measurements of NOx, O3 and Ox: Emission characteristics, inventory validation and titration effects - Xiaoxiao Zhang; Bin Yuan; Yibo Huangfu; Huizhi Liu; Thomas Karl; Ming Chang; Shiyi Chen; Tao Song; Jintai Lin; Guannan Geng; Hongjuan Li; Eran Tas (Environmental Pollution, 2025)

Spatio-temporal heterogeneity of the estuarine turbidity maximum retreat in the Changjiang river estuary under reduced sediment supply - Jie Feng; Qian Yu; Shiyi Cao; Shiyu Zhang; Tianxu Ni; Zhiyun Du; Hangjie Lin; Yunwei Wang; Ya Ping Wang (Geo-Marine Letters, 2025)

Multi-omics investigation unveils the role of Eurotium cristatum fermentation in potentiating thinned young apple pomace for colitis-induced liver disorders amelioration - Jiayao Lv; Yi Wang; Lanqi Zhou; Shiyi Zhang; Wei Song; Rui Dong; Tianqi Liu; Guoze Wang; Lin Shi (Food Research International, 2025)

Deciphering the mechanism underlying allergenicity reduction in egg white powder by pulsed electric field treatment - Luyue Huang; Shiyi Zhao; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Bioscience, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

Reproductive toxicity and molecular mechanisms of benzo[a]pyrene exposure on ovary, testis, and brood pouch of sex-role-reversed seahorses (Hippocampus erectus) - Yuanyuan Xue; Fang Wang; Xiaolei Su; Mingzhu Li; Hansheng Yan; Shiyi Zheng; Yicong Ma; Jie Dong; Yali Liu; Qiang Lin; Kai Wang (Environmental Pollution, 2025)

Foodborne iron overload induces oxidative stress and causes mitochondrial damage in the liver of grass carp (Ctenopharyngodon idellus) - Xiaoman Huang; Yan Yang; Yanhan Bai; Shiyi Yang; Bing Chen; Linpeng Zhang; Lihan Liu; Junjie Tao; Chengming Tu; Li Lin; Zhendong Qin (Aquaculture, 2025)

Development and antimicrobial activity of composite edible films of chitosan and nisin incorporated with perilla essential oil-glycerol monolaurate emulsions - Zhantong Fang; Yating Yang; Shuimu Lin; Lirong Xu; Shuyi Chen; Wanxia Lv; Nannan Wang; Shiyi Dong; Chunhong Lin; Yutao Xie; Jingru Liu; Meihan Meng; et al. (Food Chemistry, 2025)

Host-intestinal microbiota interactions in Edwardsiella piscicida-induced lethal enteritis in big-belly seahorses: Novel insights into the role of Carbohydrate-Active enzymes and host transcriptional responses - Longwu Jia; Lele Zhang; Hongwei Yang; Lin Li; Shiyi Zheng; Yicong Ma; Yuanyuan Xue; Jingyi Zhang; Mingzhu Li; Xiaolei Su; Kai Wang (Fish & Shellfish Immunology, 2025)

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

Investigating the generation mechanism of nanobubbles and the ion-transport regulation on nanofiltration membranes for efficient salt-salt separation - Shiyi Yao; Hansi Zhang; Kaiwen Wang; Lixing Lin; Xiaoxia Sun; Jia Xu (Journal of Cleaner Production, 2024)

Passive protection of chicken egg yolk immunoglobulin (IgY) against Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Linpeng Zhang; Yucong Hong; Kaihui Sun; Shuyan Zhao; Yanhan Bai; Shiyi Yang; Junjie Tao; Fei Shi; Fanbin Zhan; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

The detoxification ability of sex-role reversed seahorses determines the sexual dimorphism in immune responses to benzo[a]pyrene exposure - Kai Wang; Yuanyuan Xue; Yali Liu; Xiaolei Su; Lei Wei; Chunhui Lv; Xu Zhang; Lele Zhang; Longwu Jia; Shiyi Zheng; Yicong Ma; Hansheng Yan; et al. (Science of The Total Environment, 2024)

Mechanisms of persistent hemolysis-induced middle kidney injury in grass carp (Ctenopharyngodon idella) - Chengming Tu; Shiyi Yang; Minxuan Yang; Lihan Liu; Junjie Tao; Linpeng Zhang; Xiaoman Huang; Ye Tian; Ningjing Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Effects of feeding chicken egg yolk antibodies on intestinal cell apoptosis, oxidative stress and microbial flora of tilapia (Oreochromis niloticus) infected with Streptococcus agalactiae - Linpeng Zhang; Yanhan Bai; Junjie Tao; Shiyi Yang; Chengming Tu; Lihan Liu; Xiaoman Huang; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Shiyi Yang; Yanhan Bai; Junjie Tao; Chengming Tu; Bing Chen; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

FerrylHb induces inflammation and cell death in grass carp (Ctenopharyngodon idella) hepatocytes - Junjie Tao; Lihan Liu; Xiaoman Huang; Chenming Tu; Linpeng Zhang; Shiyi Yang; Yanhan Bai; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Immune response mechanisms underlying bacterial infection in Aquarana catesbeiana erythrocytes - Yanhan Bai; Lingqin Lu; Junjie Tao; Chengming Tu; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Aquaculture, 2024)

The infection of Aeromonas hydrophila activated Multiple programmed cell death pathways in red blood cells of Clarias fuscus - Junjie Tao; Chengming Tu; Zizheng Xu; Yanhan Bai; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Assessment of the impact of climate change on endangered conifer tree species by considering climate and soil dual suitability and interspecific competition - Wenhuan Xu; Jing Jiang; Huan-yu Lin; Tze-Ying Chen; Shiyi Zhang; Tongli Wang (Science of The Total Environment, 2023)

Establishing highly efficient absorptive and catalytic network for depolarized high-stability lithium-sulfur batteries - Jianan Wang; Xin Chen; Zhenyu Wang; Changzheng Lin; Shiyi Sun; Jianwei Liu; Yunpeng Liu; Qianyue Ma; Ling Wang; Kai Yang; Jiangtao Feng; Xi Wang; et al. (Chemical Engineering Journal, 2023)

Au/SiNCA-based SERS analysis coupled with machine learning for the early-stage diagnosis of cisplatin-induced liver injury - Shengjie Ge; Gaoyang Chen; Dawei Cao; Hechuan Lin; Ziyang Liu; Meng Yu; Shiyi Wang; Zhigang Wang; Ming Zhou (Analytica Chimica Acta, 2023)

Efficient degradation of triclosan by aluminium acetylacetonate doped polymeric carbon nitride photocatalyst under visible light - Danyan Sun; Xiaohu Lin; Jingcheng Xu; Zhibo Lu; Juwen Huang; Shiyi Li; Luiza C. Campos (Journal of Environmental Chemical Engineering, 2023)

Soil–structure interaction analysis of nuclear power plant considering three-dimensional surface topographic irregularities based on automatic octree mesh - Jianbo Li; Lei Zhou; Shiyi Li; Gao Lin; Zhixin Ding (Engineering Structures, 2023)

Successful treatment of ceftazidime/avibactam combined with aztreonam in the NDM-producing Klebsiella pneumoniae bloodstream and intestinal infections in a NK/T lymphoma patient with agranulocytosis during autologous hematopoietic stem cell transplantation: a case report - Shiyi Liu; Qingqing Lin; Lizhi Ouyang; Chengjie Zhou; Huajun Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
New Delhi metallo-beta-lactamase (NDM)-producing Klebsiella pneumoniae is increasingly reported worldwide. Clinicians face significant challenges in the treatment of this multidrug-resistant bacterium. The combination of ceftazidime/avibactam (CAZ/AVI) and aztreonam (ATM) is currently probably the most effective strategy for the treatment of such infection. We described a patient diagnosed with NK/T cell lymphoma who underwent autologous hematopoietic stem cell transplantation (ASCT) in the hematology department. The patient developed severe infection after ASCT. Blood and stool cultures showed carbapenem-resistant K. pneumoniae . Blood sample was detected as NDM-producing K. pneumoniae . We successfully treated this infection with CAZ/AVI and ATM.

Exosomes from patients with Parkinson’s disease are pathological in mice - Chao Han; Nian Xiong; Xingfang Guo; Jinsha Huang; Kai Ma; Ling Liu; Yun Xia; Yan Shen; Jie Li; Haiyang Jiang; Luxi Wang; Shiyi Guo; et al. (Journal of Molecular Medicine, 2019)

Genetic analysis of ABCG2 gene C421A polymorphism with gout disease in Chinese Han male population - Binbin Wang; Zhimin Miao; Shiguo Liu; Jing Wang; Shiyi Zhou; Lin Han; Dongmei Meng; Yunlong Wang; Changgui Li; Xu Ma (Human Genetics, 2010)